Historical policy as a tool for changing the ethnocultural situation in Silesia - Serhiienko, Vsevolod (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
This article examines the impact of historical policy on the ethnocultural situation in the Silesian region. The article analyzes various aspects of political decisions that influence the formation and transformation of ethnic and cultural identities in this region during different historical periods. Special attention is paid to the role of state institutions, legislation, and historical narratives in creating or changing ethnic boundaries and cultural practices. The article examines critical stages of Silesian history, including periods of political transformation and conflict that impacted the distribution of ethnic groups and their cultural identity. A comparative analysis of the strategies used by the authorities to change the ethno-cultural landscape is carried out, taking into account the positive and negative consequences of these interventions. The study results indicate the importance of historical policy as an instrument of active intervention in ethnocultural processes, and also emphasize the need to take this influence into account when developing modern political strategies in the context of regional development and multiculturalism.